PENINGKATAN KUALITAS TIDUR IBU HAMIL TRIMESTER III DENGAN PEMBERIAN AROMATERAPI LEMONGRASS - Wahyuni, Iin; Maria, Atik; Elly Agustina, Citra (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
Pregnancy is a physiological process, but in some conditions it can turn into pathological, and if not treated appropriately will result in mischief for the mother and fetus. (Yuliani, 2021) physiological discomfort during pregnancy that is often experienced is vomiting (emesis gravidarum) and difficulty sleeping (insomnia). (Carlin, 2022 ) in pregnancy, Other than physical changes, but also psychologically caused by hormonal.Pregnant women need enough rest, This is because most pregnant women have difficulty sleeping (insomnia) entering the end of pregnancy. Physical and emotional changes during pregnancy are the cause of complaints of difficulty sleeping in pregnant women. (Yuniata, 2022). Aromatherapy sereh effective in reducing lemons and improve the quality of sleep for pregnant women third trimester.Roll on the lemongrass aromaterapi provided directly as she visited and then during the week to evaluate in 13 other than pregnant women, 10 pregnant women (77 % ) good category 3 and pregnant women (23 %) bad category.And concluded the pregnant women reduced or mother felt more relaxed and care will be by the mother at home.